(untitled) (Biuletyn Kryminologiczny, 2020)
This article considers the problem of counteracting the illegal trade in wild fauna and ﬂora in Poland, with special regard to the social control of supply and demand of wildlife. Both social control of the demand for wild fauna and ﬂora and the control of the supply part of this phenomenon are burdened with certain drawbacks, by defnition, integrated into both models. In order to eﬀectively counteract illegal trade in wild fauna and ﬂora, it is necessary to recognize the patterns of the phenomenon and to design a social and criminal policy in this area that will be an adequate response to both the supply of the phenomenon and its demand. The main aim of the project was therefore to present the results of qualitative research conducted with experts dealing with the phenomenon of illegal trade in wild fauna and ﬂora in Poland. W artykule omówiono problem przeciwdziałania nielegalnemu handlowi dziką fauną i ﬂorą w Polsce ze szczególnym uwzględnieniem społecznej kontroli podaży i popytu na dzikie zwierzęta. Zarówno kontrola społeczna popytu na dziką faunę i ﬂorę, jak i kontrola podażowej części tego zjawiska są z defnicji obarczone pewnymi wadami, zintegrowanymi z obydwoma modelami. Aby skutecznie przeciwdziałać nielegalnemu handlowi dziką fauną i ﬂorą konieczne jest rozpoznanie wzorów tego zjawiska i zaprojektowanie takiej polityki społecznej i kryminalnej w tym zakresie, która będzie adekwatną odpowiedzią zarówno na jego podaż, jak i popyt. Głównym celem projektu było zatem przedstawienie wyników badań jakościowych przeprowadzonych z ekspertami zajmującymi się zjawiskiem nielegalnego handlu dziką fauną i ﬂorą w Polsce.